2019
DOI: 10.1016/j.toxrep.2019.06.019
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of neurotoxicity and hepatotoxicity effects of acute and sub-acute oral administration of unripe ackee (Blighia sapida) fruit extract

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…The tree belongs to the Sapindaceae family; and its fruit consists of a pod, pulp, and aril covering the seed [ 14 ]. Arils of the fruit only become edible and perfectly safe when the ripe fruit opens spontaneously to reveal the seeds (which are known to be poisonous) and the fleshy aril [ 15 ]. These edible arils are a rich source of protein, fat, and vitamins A, B1, B2, and C [ 14 ], thus, being a potential gluten-free substitute for wheat [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tree belongs to the Sapindaceae family; and its fruit consists of a pod, pulp, and aril covering the seed [ 14 ]. Arils of the fruit only become edible and perfectly safe when the ripe fruit opens spontaneously to reveal the seeds (which are known to be poisonous) and the fleshy aril [ 15 ]. These edible arils are a rich source of protein, fat, and vitamins A, B1, B2, and C [ 14 ], thus, being a potential gluten-free substitute for wheat [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A report has shown that ackee fruit may be neurotoxic and hepatotoxic if the unripe fruit is eaten. 16 Urine samples taken from two toddlers with ackee fruit poisoning revealed significant levels of methylene-cyclopropyl acetic acid, including dicarboxylic acids 2ethyl malonate, adipate, and glutarate. 17,18 However, these toxicity studies were conducted on the fruit of the plant.…”
mentioning
confidence: 98%